(∈, ∈∨q˘)-Bipolar Fuzzy b-Ideals of BCK/BCI-Algebras. (11th February 2021) - Mursaleen, M.; Balamurugan, M.; Loganathan, K.; Nisar, Kottakkaran Sooppy
Abstract : In this paper, the idea of ∈, ∈ ∨ q ˘ -bipolar fuzzy b -ideals and an ∈, ∈ ∨ q ˘ -bipolar fuzzy ideals of BCK / BCI -algebras is delivered, and their related properties are investigated with the aid of some examples. We also provide the connection between ∈, ∈ ∨ q ˘ -bipolar fuzzy ideals and bipolar fuzzy ideals and ∈, ∈ ∨ q ˘ -bipolar fuzzy b -ideals and bipolar fuzzy b -ideals by way of counterexamples.